2013
DOI: 10.1002/jpln.201200440
|View full text |Cite
|
Sign up to set email alerts
|

Silicon decreases the arsenic level in rice grain by limiting arsenite transport

Abstract: Silicon (Si) reduces arsenic (As) levels in rice shoot and grain. However, the underlying mechanisms remain unclear. In this study, we examined the effect of Si application to three rice paddy soils on the dynamics of Si, iron (Fe), phosphorus (P), and As in the soil solution, As accumulation in rice straw, flag leaf, husk, brown rice, and polished rice, and on As speciation in polished rice. Silicon application to soil increased the concentrations of Si, Fe, As, and P in the soil solution, while the redox pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(59 citation statements)
references
References 59 publications
(99 reference statements)
5
52
1
1
Order By: Relevance
“…Silicon can also alleviate the toxicity of contaminants such as As in rice (Fleck et al, 2013). The beneficial effects of Si on plant growth have been observed in previous studies by Li et al (2009a) and Fleck et al (2013) who reported that Si addition increased rice straw and grain yields. Results from this investigation have demonstrated that Si application significantly increased root (p<0.05) and grain biomass (p<0.001) (Figure 1).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Silicon can also alleviate the toxicity of contaminants such as As in rice (Fleck et al, 2013). The beneficial effects of Si on plant growth have been observed in previous studies by Li et al (2009a) and Fleck et al (2013) who reported that Si addition increased rice straw and grain yields. Results from this investigation have demonstrated that Si application significantly increased root (p<0.05) and grain biomass (p<0.001) (Figure 1).…”
Section: Discussionmentioning
confidence: 71%
“…Numerous studies have shown that silicate (Si) application not only increases rice yield, but also suppresses uptake and accumulation of As in rice grains, though Si was not considered as an essential element of rice (Li et al, 2009a;Seyfferth and Fendorf, 2012;Fleck et al, 2013). In flooded soils, rice is inherently efficient at taking up and transferring As(III) (Su et al, 2010) due to the translocation of As (III) into rice via silicon transport systems (transporters Lis1 and Lsi 2) as a silicon acid analogue (Ma et al, 2006(Ma et al, ,2008Chen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the NPK treatment, NP+S-KSi900, NP+S-KSi9000, and NPK+ CaSi9000 treatments significantly reduced As concentration in rice grain. This inhibitory effect of Si is supported by many laboratory experiments (Bogdan and Schenk 2008;Li et al 2009;Fleck et al 2013;Tripathi et al 2013). Areao et al (2009) reported that the soil Eh value decreased rapidly during the flooded period.…”
Section: Discussion Effect Of Si On As Concentration In Rice Grainmentioning
confidence: 74%
“…Arsenite, the most prevalent form of arsenic in flooded rice paddies, is a silicic acid analogue, and is taken up by rice roots due to its similarity to silicic acid [205,206,214,304,305]. Several authors have shown that when excess silicon is available in the soil or in hydroponic culture, arsenic uptake and translocation to plant shoots and rice grain are reduced [207,210,214,306,307]. Organic forms of arsenic also are taken up by rice, via the silicic acid pathway [207,305].…”
Section: Silicon In Soilsmentioning
confidence: 99%